Prevalence of Canine Parvo Viral Infection in Dogs in andaround Junagadh District of Gujarat State - Sherasiya, Raisudin M; Vagh, Arshi A; Bilwal, Avinash K; Damor, Jayendra R; Parmar, Vijay L; Dodiya, Piyush G; Baria, Vinay R; Patel, Priyanshi V (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
A detailed study was conducted from October-2022 to March-2023 at the Veterinary Clinical Complex, Kamdhenu University, Junagadh, Gujarat involving screening of 817 dogs for presence of canine parvo viral infection via Rapid test kit and PCR. The prevalence of canine parvo virus in dogs was recorded as 4.77 % (39/817). Higher prevalence of parvovirus infection was recorded in dogs with age <3 months (53.84%). It was high in male dogs (56.41%) and in the month of December (38.46%). The prevalence was also found higher in non-descript breed (30.76%), in non-dewormed dogs (61.53%) and in non-vaccinated dogs (92.30%) compared to their counterparts. The findings highlight the influence of various factors on the prevalence of CPV and the level of awareness among pet owners of the region regarding prevention of this disease in their pets.